2021
DOI: 10.1016/j.ultrasmedbio.2021.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elastography in the Assessment of the Stiffness of Spastic Muscles: A Systematic Review

Abstract: The incidence of muscle spasticity is high in patients with diseases of the central nervous system. This condition leads to significant limitations in movement and impaired functional capacities. Muscle spasticity manifests as changes in the mechanical properties of the muscles. This muscle disorder is generally assessed using qualitative methods, whose validity, reliability and sensitivity are questionable. In recent years, ultrasound elastography (USE) has been used as a non-invasive technique for characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…Other authors observed poor correlation [8]. A recent systematic review showed moderate to good correlations between stiffness assessed by ultrasound elastography and hyper-resistance assessed by the MAS, ranging from 0.55 to 0.85 [32]. However, the technique only evaluates elasticity, which relates to non-neural components of hyper-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors observed poor correlation [8]. A recent systematic review showed moderate to good correlations between stiffness assessed by ultrasound elastography and hyper-resistance assessed by the MAS, ranging from 0.55 to 0.85 [32]. However, the technique only evaluates elasticity, which relates to non-neural components of hyper-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Another frequent method employed was the use of myometers which mechanically determine parameters of stiffness through tissue percussion. Although these non-invasive techniques are able to assess tissue stiffness, limitations to these methods are the lack of standardized protocols, intra- and inter-operator differences during the assessment procedures and the common but fallacious consideration that muscles and tendons are homogeneous entities; therefore, differences in assessment locations may provide heterogeneous data [ 135 ].…”
Section: Limitations and Methodological Considerationsmentioning
confidence: 99%
“…This technique has promise as a noninvasive, quantitative measure for spasticity that could be applied to diverse anatomical regions not traditionally studied by quantitative measures (e.g., trunk, bulbar muscles) 33 …”
Section: Assessing/quantifying Spasticitymentioning
confidence: 99%